Pathological manifestations on hospital unit facades: case study at the appointment center of the Oswaldo Cruz University Hospital, Recife - PE - Costa, Lorena Vila Bela; Teixeira, Bruna Correia; Monteiro, Eliana Cristina Barreto; Soares, Willames de Albuquerque (Revista Nacional de Gerenciamento de Cidades, 2024)
Facades separate the internal environment from the external environment of a building, being the element that suffers most from the action of environmental agents and, therefore, requires monitoring to guarantee its performance. In this analysis and recording process, the Damage Map can be a valuable technique as it deals with a set of documents that graphically represent problems presented by construction. With the aim of expanding the applicable contexts for the Damage Map and promoting a contribution to the University of Pernambuco, the present research aimed to determine the pathological manifestations occurring on the facades of the marking center block of the Oswaldo Cruz University Hospital, Recife -PE, see the presentation of their respective Damage Maps and corrected region damage factors (FDrc). The methodology involved carrying out research into the history of the building, field inspections with the aid of a fissurometer, laser tape measure and pacometer and the application of equations to calculate the FDrc in order to have a quantitative analysis. With the development of the study, it was found that the Damage Map technique has value in helping to make decisions for the maintenance plan, that with the calculation of damage factors it is possible to evaluate the degradation in relation to the regions of the facades, with the identification of possible factor relationships, and that the most common pathological manifestations were mold, mildew and dirt.